MODERASI DAULAH RUSTAMIYYAH DALAM PENYELESAIAN KONFLIK POLITIK - Rofiq, Ahmad Choirul (Universitas Islam Negeri Raden Intan Lampung, 2014)
MODERATE POLICY OF DAULAH RUSTAMIYYAH IN RESOLVING POLITICAL CONFLICTS. Disputes due to conflict of interest are unavoidable phenomena particularly in political life. Political conflicts arise due to differences of opinion, competition, and conflicts between a number of individuals, groups, or organizations involving state officials. This paper seeks to uncover the pattern of political conflict resolution carried by Daula Rustamiyyah which incidentally belonged to Khawarij Ibadiyyah moderate wing. By using the historical approach, the author finds out that the political policy of Rustamiyyah to resolve political conflicts within the government were based on Ibadiyyah doctrines that promote moderation. A number of political conflicts were successfully resolved by Rustamiyyah with a minimum violence. To solve political conflicts, the Rulers of Rustamiyyah began with persuasive step, from admonition to threat. Then, if necessary, it involves a third party as a mediator. If the measures were all unsuccessful, they took a firm stance, especially against those who endanger public stability. In addition, the government often took the initiative to utilize diplomacy during the ongoing armed conflict. By implementing such policies, peace and stability can be maintained by the Rustamiyyah government.